Phytoremediation of heavy metal pollution: Hotspots and future prospects - Yang, Le; Wang, Junbang; Yang, Yongsheng; Li, Sha; Wang, Tongxin; Oleksak, Patrik; Chrienova, Zofia; Wu, Qinghua; Nepovimova, Eugenie; Zhang, Xiujuan; Kuca, Kamil (Ecotoxicology and environmental safety, 2022)
To clarify the global status and research hotspots of heavy metal pollution phytoremediation, we used Web of Science, Cite Space software, and VOS viewer to analyse 1123 publications from the period of 2000–2020. Literature categories, research hotpots, and the most prolific publications by country, institution, and author were analysed separately. Around 34% of the articles are contributed from five countries: China (29.37%), India (11.00%), Spain (6.29%), Italy (6.20%), and Pakistan (5.67%). The hot research topic keywords were “diversity”, “translocation”, and “enhanced phytoremediation”. Cadmium was the most highly concerned heavy metal in the phytoremediation. Twenty-three articles were highly cited, and they mainly focused on 1) enhancing the remediation ability of plants in heavy metal contaminated soil by microbial and chemical additives; 2) the molecular effect and mechanism of heavy metals on plant growth and development; 3) discovering novel heavy metal hyper-enriched plants which can remediate mixed heavy metal pollution. From the above analysis, we concluded that the future research directions should be 1) strengthening the plant remediation ability by biochemical means; 2) studying the molecular mechanism underlying heavy metal damage to plants; 3) studying the enrichment principle of plants for heavy metals. The present study provides a further understanding of the trends in phytoremediation of heavy metal pollution, and the data analysed can be used as a guide for future research directions. •Trends and research hotspots of heavy metal phytoremediation were investigated.•China, India, Spain, Italy, and Pakistan contributed to 34% of all analysed articles.•Cadmium was the most highly concerned heavy metal in phytoremediation.•Research should focus on strengthening phytoremediation ability by biochemical means.•Studies on heavy metal damage to plants and enrichment principle of plants are needed.